Mode of conception of triplets and high order multiple pregnancy in Dublin – a 10-year review. (16th November 2010) - Basit, I; Johnson, S; Mocanu, E; Geary, M; Wingfield, M; Daly, S
Abstract : The aim of this study was to know the mode of conception of triplet and high order multiple (HOM) pregnancies with a view to determining means of reducing their incidence. An audit was performed of all triplet and HOM pregnancies delivered in Dublin's three teaching hospitals over a 10 year period (1999 to 2008). The mode of conception for each pregnancy was studied. 92 triplet, 9 quadruplet and 1 quintuplet pregnancies occurred, representing respectively 0.04%, 0.003% and 0.0004% of total births (226 792) at the 3 hospitals. Information regarding the mode of conception was available for 83 (81%) pregnancies and is shown in the table. Of those treated with IVF/ICSI/FET, 2 embryos were transferred in 8 cases (28%), 3 in 12 cases (41%) and the number was not recorded for 15 cases (31%). The quintuplets, 2 (22%) quads and 12 (13%) triplets resulted from clomiphene treatment. Conclusion: Triplet and HOM pregnancies are a major cause of maternal, fetal and neonatal morbidity. Many are iatrogenic, arising from fertility treatments. A worrying number occur following treatment with clomiphene citrate. Reducing the numbers of embryos transferred will address IVF/ICSI-related multiple pregnancy rates and this is currently happening in Ireland. However, the prescription of agents such as clomiphene citrate or FSH/HMG, is less well regulated and audited. These drugs should only be prescribed when appropriate resources are available to monitor patients adequately. Mode of conception Triplet pregnancies Quadruplet pregnancies Spontaneous 26 2 Clomiphene 12 2 IUI 3 2 IVF/ICSI 33 0 Unknown 16